(untitled) (Journal of Engineering, 2006)
The present work investigates the effect of some of the variables in spot tungsten inert gas shielded welding (TIG Spot) for (Aluminum-Magnesium) alloy type(5052-O) which is non–heat treatable alloy for its wide industrial uses and applications in field of welding technology. TIG Spot welding was performed by using tungsten electrode (EWTh2)of diameter (3.2mm) and DC current with direct polarity (DCSP) at constant shielded gas flow rate (15litre/min). The welded specimens were tested by using the Instron machine to determine the maximum shear force (shear strength ) of spot welded and to define the optimum conditions of spot welding variables in relation to the weld current, weld time and arc length of welding to produce an acceptable weld. The metallurgical changes of the weld zone and heat affected zone were studied under optimum conditions of welding. It has been shown that the increase in the welding current and welding time tends to increase the maximum shear force and it reaches maximum value and then decreases with high currents and long times. The maximum shear force was 2.4KN at welding current of (90) Amp , welding time ( 7)sec and arc length (1.6mm ) for 1mm thickness. It was also found that the highest value of hardness ( 53.5 Hv) was at the center of the spot welded and decreases gradually from the center of the weld spot towards the base metal.